Bacterial Endosymbionts Identified From Leafhopper (Hemiptera: Cicadellidae) Vectors of Phytoplasmas. Issue 2 (4th March 2023) - Cooper, William Rodney; Walker, William B; Angelella, Gina M; Swisher Grimm, Kylie D; Foutz, Jillian J; Harper, Scott J; Nottingham, Louis B; Northfield, Tobin D; Wohleb, Carrie H; Strausbaugh, Carl A
Abstract: Insects often harbor bacterial endosymbionts that provide them with nutritional benefit or with protection against natural enemies, plant defenses, insecticides, and abiotic stresses. Certain endosymbionts may also alter acquisition and transmission of plant pathogens by insect vectors. We identified bacterial endosymbionts from four leafhopper vectors (Hemiptera: Cicadellidae) of 'Candidatus Phytoplasma' species by direct sequencing 16S rDNA and confirmed endosymbiont presence and identity by species-specific conventional PCR. We examined three vectors of Ca. Phytoplasma pruni, causal agent of cherry X-disease [ Colladonus geminatus (Van Duzee), Colladonus montanus reductus (Van Duzee), Euscelidius variegatus (Kirschbaum)] – and a vector of Ca. Phytoplasma trifolii, the causal agent of potato purple top disease [ Circulifer tenellus (Baker)]. Direct sequencing of 16S identified the two obligate endosymbionts of leafhoppers, 'Ca. Sulcia' and ' Ca. Nasuia', which are known to produce essential amino acids lacking in the leafhoppers' phloem sap diet. About 57% of C. geminatus also harbored endosymbiotic Rickettsia . We identified 'Ca. Yamatotoia cicadellidicola' in Euscelidius variegatus, providing just the second host record for this endosymbiont. Circulifer tenellus harbored the facultative endosymbiont Wolbachia, although the average infection rate was only 13% and all males were Wolbachia- uninfected. A significantly greater percentage of Wolbachia- infected Ci. tenellus adults than uninfected adults carried Ca. P. trifolii, suggesting that Wolbachia may increase this insect's ability to tolerate or acquire this pathogen. Results of our study provide a foundation for continued work on interactions between leafhoppers, bacterial endosymbionts, and phytoplasma.